Predicting consumer switching decisions: the trust paradox and its impact on the efficiency of sustainability-label and food chain brands - Xuemei Dong; Baichen Jiang; Fallah Samuel Kassoh; Feiyu Chen (Sustainable Futures)
Carbon emission reduction in food supply chains requires consumers to shift from status quo maintenance toward sustainable practices. Existing literature shows such transitions remain challenging unless a dominant attribute emerges, providing sufficient justification for switching. While trust plays a pivotal role in food quality attributions, the interaction between consumer trust and dominant attribute selection remains underexplored. This study examines how consumers choose between maintaining the status quo and adopting sustainable alternatives through distinct trust mechanisms: abstract trust in ecological certifications versus interpersonal trust in food chain actors. Using conjoint analysis with 4,929 consumers, we reveal a nuanced trust hierarchy. Ecological certifications demonstrate superior effectiveness compared to food chain brands, emerging as the dominant switching catalyst during abstract trust reconstruction. However, this pattern reverses when consumers seek comprehensive quality assurances throughout the supply chain. Trust exhibits differential effects across actors, with only farmer trust consistently accelerating switching decisions regardless of dominant attribute presence. Our findings advance food decision-making literature by demonstrating that apparent preference inconsistencies reflect an underlying hierarchical switching process. This process initiates through abstract trust establishment, subsequently enhanced by interpersonal trust flexibility. These insights illuminate theoretical mechanisms governing sustainable food transitions and provide actionable frameworks for policy interventions.